Efeitos do treinamento de força na massa muscular e funcionalidade de idosos: uma revisão de literatura - Sentanin, Lívia Maria (Universidade Federal de São Carlos, 2025)
Population aging is one of the most relevant phenomena of the 21st century, with sarcopenia being one of the main physiological challenges associated with old age. Strength Training (ST), or Resistance Training (RT), emerges as a central and effective intervention, demonstrating vast benefits for the elderly population. This training is a safe, feasible, and dose-dependent exercise modality that establishes itself as the fundamental intervention to mitigate the deleterious effects of aging. This literature review aimed to analyze the effects of Strength Training (ST) on muscle mass and functionality in the elderly, addressing musculoskeletal adaptations and the systemic benefits of Resistance Training (RT) as a primary intervention in combating the challenges of aging, such as sarcopenia. The reviewed literature confirms that ST, frequently applied in progressive and individualized protocols, is effective in preserving and/or increasing muscle mass and strength. Progressive manipulation of intensity and volume (with high intensity and high volume demonstrating greater effectiveness) results in improved strength, functional performance, and quality of life, being essential for maintaining independence and promoting healthy longevity in older adults, including the frail and those with comorbidities.
Effects of strength training on muscle mass and functionality in older adults: a literature review
Keywords: Treinamento; Idoso; Training; Elderly; Sarcopenia; CIENCIAS DA SAUDE::EDUCACAO FISICA; 3. Saúde e Bem-Estar